Answer:
Yes
Step-by-step explanation:
f(x) = x³ − 9x² + 11x + 21
f(3) = (3)³ − 9(3)² + 11(3) + 21
f(3) = 27 − 81 + 33 + 21
f(3) = 0
Answer:
D
Step-by-step explanation:
brainliest pls
Step-by-step explanation:
3x - 5x - 4 - x^2 + 12x - 17x^2 - 16
= -2x - 20 - 18x^2 + 12x
= 10x - 20 - 18x^2
Hope it helpz~ uh..
Answer:
a. 450 b. 10078.9097
Step-by-step explanation:
a. go with the formula W=FD
F= force
W= work done
D= distance
b. go with the formula F=mgcos(x)
M= mass
G= gravity constant (9.8)
then get to the normal formula of W=FD after getting the Force
Text my number ( 4015166761) i did all of that already im in 7th ill hook u up wit all the answers .